Plasma lipoproteins - Gotto, Antonio M., Jr (New comprehensive biochemistry ;, 1987)
In this rapidly evolving field of research, an enormous amount of new knowledge of lipoprotein structure, function and metabolism has emerged. The 1985 Nobel Prize-winning pioneering work of Brown and Goldstein on the LDL receptor has had a profound impact on developments in the field. This work is one of the many subjects reviewed in detail in this book. The volume begins with chapters on structure, then proceeds to analysis of lipid and lipoprotein dynamics, metabolism, function, genetics, and molecular biology. Lipoprotein genetics in molecular biology, the role of lipoprotein receptors, and Lp(a) - a topic underrepresented in volumes on lipoproteins, are another three such topics in an impressive volume. This work will mainly be of interest to researchers interested in lipid and lipoprotein structure and metabolism, but will also be of great value to clinical medicine and biology in general.